2020
DOI: 10.1093/trstmh/traa044
|View full text |Cite
|
Sign up to set email alerts
|

An observational report of universal GeneXpert testing of inpatients with diagnosed or presumptive TB in the Philippines

Abstract: Background The Philippines is a high TB and multidrug-resistant TB burden country. Although the scale-up of GeneXpert testing is occurring, the benefits of universal Xpert-Mycobacterium tuberculosis/ rifampicin (MTB/RIF) testing in inpatients have not been documented. Methods Routine GeneXpert testing irrespective of priority criteria for testing was conducted within a prospective cohort of all adults with known or presumptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…All the research showed similar results compared to our research outcomes. These studies concluded that the application of the Gene-Xpert MTB/ RIF assay showed dramatic improvements for the rapid detection of tuberculosis and drug resistance, which offers promising advancements in TB control programs [53][54][55][56][57][58][59][60].…”
Section: Plos Onementioning
confidence: 99%
“…All the research showed similar results compared to our research outcomes. These studies concluded that the application of the Gene-Xpert MTB/ RIF assay showed dramatic improvements for the rapid detection of tuberculosis and drug resistance, which offers promising advancements in TB control programs [53][54][55][56][57][58][59][60].…”
Section: Plos Onementioning
confidence: 99%
“…by Gautam et al [11] (26.1%) and Mondal et al [12] (8.91%). In addition, other countries in Asia, showed higher prevalence of RR as in Pakistan [13] (10.2%), Philippines [14] (19.3%), China [15] (5.9%). The difference between our rate and the previous rates may be due to that India and China are countries with high TB burden while Egypt is one of the low/middle TB burden countries.…”
Section: Resultsmentioning
confidence: 96%